The New Iconic Landmark of Bali in 2023: Turyapada Tower KBS 6.0 Kerthi Bali - I Gusti Made Andrian Sumantri (Bali Tourism Journal, 2022)
As an effort to erase multiple blank spots in the north, east, and west parts of Bali Island, The Bali Provincial Government worked on an integrated communication tower project in Pegayaman Village, Buleleng Regency. The Tower with the name Turyapada would be the next international-level landmark in the Buleleng district. Turyapada tower is an integrated communication building that aims as a transmitter to erase multiple blank spots in Buleleng, Jembrana and Karangasem areas. Built at an altitude of 1,521 meters above sea level, the tower would have cutting-edge facilities to support its operation as a communication tower and tourism object. The building concept is designed as a green building, reflecting the relationship between nature and Balinese culture. The architecture and technology of this building are designed to be environmentally friendly. Constructed on an area of 13,767.7 m2, the tower park is divided into six zones: the educational zone, communal zone, commercial zone (UMKM), recreational zone, management zone, and plantation zone. The tower’s center area would provide various educational facilities, such as a planetarium, a skywalk glass bridge, and a 360-degree rotating restaurant. In the vicinity, planned to be gardens for flowers, orchards, children's play areas, glamping, flying fox, SMEs arcades, and restaurants. For the visitor’s convenience, a 1-hectare parking area has been prepared, and a gondola to carry the visitor 1.4 km from the parking area to the main tower. The facilities are expected to provide new jobs and become a new economic growth center for the local area.